The First Latin Textbook in Armenian - MKRTCHYAN, NELLI (Bulletin of Yerevan University B: Philology, 2021)
The article is devoted to the description of the textbook by Ed. Aghayan “The Grammar of the Latin Language” (morphology). Following the principles of structural linguistics, Ed. Aghayan tried to present a comprehensive and consistent analysis of this ancient language with utmost diligence. The description of phonetic facts is followed by a characterization of morphological features of the parts of speech in Latin, ranging from grammatical categories of essential parts of speech to their partial syntactic usage. Apart from its practical purpose, this textbook is highly valued for providing the learners with an important insight into the classical grammatical terminology and the corresponding equivalents in Armenian.